The Role Of Management Skills In Enhancing Financial Decision-Making Among Micro, Small, And Medium Enterprises - Erwin Ernestus Kadar Slamet; Selvi Agustina; Taufan Herjanto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This research aims to investigate the role of management skills in enhancing financial decision-making among Micro, Small, and Medium Enterprises (MSMEs). The study employs a purposive sampling technique to select participants representing various sectors and geographical locations. A semi-structured interview model is utilized to gather data, allowing for an in-depth exploration of participants' perspectives and experiences. Data analysis involves thematic analysis to identify patterns and themes regarding the influence of management skills on financial decision-making within MSMEs. The findings highlight the significance of effective management skills, such as financial literacy, strategic planning, and risk management, in improving the financial decision-making processes of MSMEs, thereby contributing to their overall sustainability and growth. ]